Analysis of antibody dynamics in Chinese children aged 1-3 years after single-dose varicella vaccination: A 42 months prospective study - Xiang Sun; Lei Zhang; Zhiguo Wang; Wen Wang (Taylor & Francis Group, 2024)
In China, children aged 12 months receive only a single dose of the varicella vaccine and the incidence of varicella remains high. This study aims to evaluate the changes in immunity among children aged 1-3 years following a single dose of the varicella vaccine, providing a scientific basis for determining the optimal age for a second vaccination. This prospective cohort study employed glycoprotein enzyme-linked immunosorbent assay (gpELISA) for antibody detection. The changes in IgG antibody levels over time post-vaccination were analyzed using a restricted cubic spline (RCS) fitted binary logistic regression model. Varicella surveillance data were collected from the National Notifiable Disease Reporting System (NNDRS). Following a peak in varicella incidence in 2019, the incidence shifted toward older age groups. The cohort study results revealed a seropositivity rate of 100% in children during the 18 months post-vaccination, which subsequently declined to 71.6% by the 42 months. The geometric mean concentration (GMC) decreased from 307.6mIU/mL to 115.2mIU/mL. Additionally, 14 children contracted varicella during the follow-up period, resulting in a breakthrough rate of 2.85%. RCS analysis indicated that antibody levels fell below the protective threshold 18.69 months post-vaccination, with a non-linear decline in the odds ratio(OR) of maintaining antibody concentrations ≥ 50mIU/mL(p < .001, Pnonlinear ≤ 0.001). This study demonstrates that the long-term protective efficacy of a single dose of the varicella vaccine diminishes over time in children, underscoring the necessity of implementing a two-dose vaccination strategy. The findings provide scientific evidence for determining the optimal timing for administering the second dose of the vaccine.